The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.21273/jashs.104.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Siberian C Rootstock Delays Bloom of Peach 1

Abstract: Siberian C seedling rootstock delayed the bloom of 3 cultivars of peach (Prunus persica (L.) Batsch) as compared to seedling rootstocks Harrow Blood, Lovell, and Halford. Starting about 1 month before bloom, trees on Siberian C developed more slowly than those on other rootstocks as measured by flower bud moisture content. Bloom was delayed 5 days by Siberian C in both 1977 and 1978, with no adverse side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…However, there was a 4 day delay of bloom with cultivars propagated on Siberian C (Table 2). This delay in bloom development is associated with a delay in the increase in flower bud moisture content (14) and, in the present study, a delay in the increase in xylem water potential was observed.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…However, there was a 4 day delay of bloom with cultivars propagated on Siberian C (Table 2). This delay in bloom development is associated with a delay in the increase in flower bud moisture content (14) and, in the present study, a delay in the increase in xylem water potential was observed.…”
Section: Discussionsupporting
confidence: 69%
“…The present study investigates the chilling completion date in more detail by monitoring the meiotic stage of the pollen mother cells. The previous report (14) also fol lowed the change in flower bud moisture content as the buds developed from dormancy to full bloom. Here we report on fur ther investigations into rootstock effects on the changing water status of the peach tree and its relation to flower development from dormant buds to petal fall.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The effect on shoot growth was not reported. Although timing of spring budbreak appears to be determined primarily by the scion (4), rootstock influences on scion budbreak have been reported in pear (21), peach (23), and apple (3). Very little has been done to investigate the effects of chilling the root during dormancy on budbreak and resumption of shoot growth.…”
mentioning
confidence: 99%